The Credit Risk in Stock-Based Loans - Korula, Febin (African Institute of Financial Markets and Risk Management, 2019)
Stock-based loans are an increasingly popular form of loan that are collateralised using stocks. Since these loans are often non-recourse loans, the lenders are subject to the risk that the collateral is worth less than the loan, and the borrower defaults. This dissertation will consider the credit risk faced by lenders when issuing these loans. To achieve this, this dissertation will propose different models to quantify this risk using various credit measures. A sensitivity analysis to key model parameters is then conducted. Some brief comments about capital requirements will also be made.